Optimizacijski postopek v procesu zasnove zobnikov - Ulaga, Samo (Strojniški vestnik, 2001)
In this paper a tooth-geometry optimisation feature is proposed, which is to be added to the general gear-design procedure, so as to provide reduced and equally distributed wear and pitting of mating gear-teath flanks. Two principal geometry-dependent parameters are considered for the optimisation purposes: contact stress and relative sliding. Both depend on the geometry of the contacting surfaces, which is mainly influenced by the addendum modification coefficient. To maxmise the service life of the gear pair, optimum values of this coefficient have to be chosen, in order to satisfy prescribed criteria for specific sliding and Hertz pressure while all the design boundary conditions are fulfiled. An adaptive-grid-refinement algorithm procedure is applied and the gear-flank geometry resulting from the optimisation algorithm is subsequently analysed. The sliding, circumstances are compared and evaluated. A FEM contact algorithm using the Lagrange multiplier method and a spline-based geometry definition is applied to calculate the contact stress distribution patterns and to show the applicability of the computational methods to the general gear design.
Keywords: zasnove zobnikov; drsenje relativno; optimiranje; problemi kontaktni; zobniki; drsenje